Ginsenoside Rg3 micelles mitigate doxorubicin-induced cardiotoxicity and enhance its anticancer efficacy - Lan Li; Jingyu Ni; Min Li; Jingrui Chen; Lifeng Han; Yan Zhu; Deling Kong; Jingyuan Mao; Yi Wang; Boli Zhang; Meifeng Zhu; Xiumei Gao; et al. (Taylor & Francis Group, 2017)
Doxorubicin (DOX) is one of the most effective chemotherapy agents used in the treatment of hematological and solid tumors, however, it causes dose-related cardiotoxicity that may lead to heart failure in patients. One of the major reasons was increased reactive oxygen species (ROS) production. Ginsenoside Rg3 (Rg3), was powerful free radical scavengers and possessed cardioprotective effects. Nevertheless, Rg3 has low aqueous solubility and oral bioavailability, limiting its effects. Herein, we encapsulated Rg3 through spontaneous self-assembly of Pluronic F127 to improve its solubility and oral bioavailability. Moreover, co-administering Rg3 in Pluronic F127 micelles with doxorubicin can mitigate the cardiotoxicity, with ameliorating mitochondrial and metabolic function, improving calcium handling, and decreasing ROS production. In addition, it can improve the anticancer efficacy of doxorubicin. Therefore, our study provides a rational strategy for further developing a potentially viable adjunct-supportive treatment for reducing toxicity and increasing efficiency on chemotherapy.